ศึกษาการใช้งานอุปกรณ์หนุนเท้าในผุ้ป่วยส้นเท้าอักเสบ - สุนทร วงษ์ศิริ (มหาวิทยาลัยสงขลานครินทร์, 2023)
The purpose of this study was the comparison of results of plantar fasciitis treatment between a group using the PSU heel cushion and a group not using the PSU heel cushion.